Designing Number Learning Applications and Early Childhood Mathematics Calculations - Al Hafiz, Nofri Wandi; Nopriandi, Helpi (Politeknik Ganesha Medan, 2019)
The progress of technological development in the current era is very fast and fast, it is seen from how people use the technology, even now technology has entered the world of education in terms of the teaching and learning process, with the process of learning and teaching that is still focusing teachers as a material giver, it will make the learning and teaching experience monotonous and less attractive so that students become bored and lack enthusiasm especially with math lessons that use a lot of thoughts, unless the teacher can bring the class atmosphere to be interesting it will make the classroom atmosphere become enthusiasm, to help teachers in the teaching process, it is necessary to make an application that can help teachers to make students interested in learning mathematics.